An asymptomatic radiology finding with surgical indication - Saha, Kaushik; Jash, Debraj; Maikap, Malay Kr. (Journal of Advances in Internal Medicine, 2012)
DOI: http://dx.doi.org/10.3126/jaim.v1i2.6529 Journal of Advances in Internal Medicine 2012;01(02):69